Study of influential parameters of the sphere indentation used for the control function of material properties in forming operations - Satošek, Roman (Strojniški vestnik, 2019)
The uncertainties of modern, adaptable sheet metal forming systems are classified into model errors and disturbances. To improve the control of production, disturbances in the forming process need to be reduced. For this purpose, a new data flow system was introduced. It connected the data flow of all influencing material parameters into the "material property control function". To control on-line the forming production line and acquire necessary material data, an indentation test was implemented. The main parameters to follow in this test are pile-up or sink-in values after the embossing of the ball-shaped tool into the material where the innovative approach of fully anisotropic material description was used. To set-up an optimal indentation test, parametric studies were performed with material data of AW 5754-H22. Finite element simulations were used to evaluate the influences of indenter diameter, contact friction and forming history of used the material. Fully anisotropic material behaviour was considered. Novel to this approach were a) the linking of the linear correlation of pile-up with the indentation depth described by gradient k, and b) the linking of gradient k with different pre-strains by a new power function.
Keywords: anisotropy; anizotropija; forming process; indentation test; on-line control system; parametric studies; parametrične študije; preoblikovanje; sprotni nadzor sistema; test utiskavanja